ANALISIS BELANJA LANGSUNG DAN PELAPORANNYA PADA DINAS KESEHATAN KABUPATEN TEMANGGUNG - Jazilah, Faridatul; Panggiarti, Endang Kartini (Universitas Ahmad Dahlan, 2020)
The purpose of this study is to analyze direct expenditure and reporting to the Health Office. The data used is secondary data. Data collection techniques using documentation in the form of financial statements of the Health Office. The method used is quantitative descriptive method. The results of the study showed that the Health Office in Temanggung Regency had already realized the direct expenditure budget and reported in accordance with PP No. 71 of 2010.